Nutritional status of cotton plants under fertigation with reuse water and phosphate fertilization - Francisco Gonçalo Filho; Miguel Ferreira Neto; Nildo da S. Dias; José F. de Medeiros; Cleyton dos S. Fernandes; Francisco V. da S. Sá (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Water reuse is an important practice in water resource management especially in arid and semi-arid areas. The objective was to evaluate the mineral composition and boll weight of upland cotton (cultivar BRS 335) plants under fertigation with domestic sewage effluent and phosphate fertilization. An experiment was carried out using randomized block design in a 3 × 2 factorial scheme with six repetitions. Cotton plants were fertigated with three fertigation solutions containing domestic sewage effluent (RW) and supply water (SW) in the proportions of 100% SW - T1, 50% SW + 50% RW - T2 and 100% RW - T3, and two phosphate fertilizer managements (with and without phosphate fertilization at pre-planting). Macronutrient and micronutrient concentrations in the shoots and boll weight were measured and evaluated. Fertigation utilizing reuse water is able to supply both water and part of the nutritional demand of cotton plants. Calcium, copper, iron and zinc concentrations in cotton leaves were below the optimum range for the crop. Reuse water did not meet the total requirements of Ca, Cu, Fe and Zn of cotton, so complementary mineral supplementation with these nutrients is recommended for the crop to obtain high yield.